An Ambient Assisted Living Technology Platform for Informal Carers of the Elderly - iCarer - Lotfi, Ahmad; Langensiepen, Caroline; Moreno, Pedro A.; Gómez, Enrique J.; Chernbumroong, Saisakul (EAI Endorsed Transactions on Pervasive Health and Technology, 2017)
For most families with elderly relatives, care within their own home is by far the most preferred option -both for the elderly and their carers. However, frequently these carers are the partners of the person with long-term care needs, and themselves are elderly and in need of support to cope with the burdens and stress associated with these duties. When it becomes too much for them, they may have to rely on professional care services, or even use residential care for a respite. In order to support the carers as well as the elderly person, an ambient assisted living platform has been developed. The system records information about the activities of daily living using unobtrusive sensors within the home, and allows the carers to record their own wellbeing state. By providing facilities to schedule and monitor the activities of daily care, and providing orientation and advice to improve the care given and their own wellbeing, the system helps to reduce the burden on the informal carers.